Iacopo Sannazaro anche the Creation of a Poetic Canon in Early Modern England - Alessandra Petrina (Parole Rubate, 2016)
This article investigates the circulation and fame of Sannazaro’s Arcadia in early modern England, focusing first on Philip Sidney’s reception of the poem as part of an ongoing pastoral tradition. Sannazaro’s work thus contributed to create a new poetic context and decisively influenced Sidney’s own Arcadia. Significantly enough, after Sidney’s death the name of Sannazaro seems to suffer a deliberate act of ostracism (he does not appear in the works of Sidneian followers and commentators) as if Sidney’s scribal community preferred to exalt the name of their friend and patron by marginalizing one of Sidney’s sources.